Dukungan Sosial terhadap Psychological Well-Being Mahasiswa dari Keluarga Bercerai - Sri Setyoningsih; Hetti Sari Ramadhani; Adnani Budi Utami (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Students from divorced families are a vulnerable group prone to a decline in psychological well-being due to emotional and social instability within the family. This study aims to investigate the relationship between social support and psychological well-being among students from divorced families. A quantitative approach using a correlational method was chosen for this study. The sample consisted of 335 students from the University of 17 August 1945 Surabaya aged 18–25 years, selected using purposive sampling. The instrument used was a questionnaire that had undergone a series of validity and reliability checks. Data were analyzed using Pearson's correlation test. The results showed a positive and significant relationship between social support and psychological well-being (r = 0.870; p < 0.05). The findings indicate that the higher the level of social support received by students, the higher their psychological well-being. This study emphasizes the importance of social support as a protective factor in maintaining the psychological balance of students from divorced families, and serves as a basis for developing contextual interventions in higher education settings. Keywords: Social Support; Psychological Well-Being Abstrak Mahasiswa dari keluarga bercerai merupakan kelompok rentan terhadap penurunan psychological well-being akibat ketidakstabilan emosional dan sosial dalam keluarga. Penelitian ini bertujuan mengetahui hubungan dukungan sosial dengan psychological well-being pada mahasiswa yang berasal dari keluarga bercerai. Pendekatan kuantitatif dengan metode korelasional dipilih pada penelitian ini. Sampel sejumlah 335 mahasiswa Universitas 17 Agustus 1945 Surabaya berusia 18–25 tahun, yang dipilih dengan teknik purposive sampling. Instrumen yang dipakai adalah kuesioner yang telah melalui serangkaian alur validitas serta reliabilitas dengan baik. Data dianalisis dengan uji korelasi Pearson. Hasilnya menunjukkan adanya hubungan positif dan signifikan antara dukungan sosial dan psychological well-being (r = 0,870; p < 0,05). Temuan menunjukkan semakin tinggi dukungan sosial yang diterima mahasiswa, semakin tinggi pula tingkat psychological well-being yang dimiliki. Penelitian ini menekankan pentingnya dukungan sosial sebagai faktor pelindung dalam menjaga keseimbangan psikologis mahasiswa dari keluarga bercerai, serta menjadi dasar pengembangan intervensi yang kontekstual di lingkungan pendidikan tinggi. Kata kunci: Dukungan Sosial; Psychological Well-Being